Can justice be embodied in sexist language? A challenge to the Confession of Belhar - Landman, C (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
This article poses the question why the Confession of Belhar was not written in inclusive language, since it was accepted at the 1986 synod of the Dutch Reformed Mission Church, which succeeded the 1982 synod where women were restored to the office of minister. It argues that the concept of justice is presented at an advanced level in the Confession of Belhar; however, it is regrettable that in this confession justice is embodied in sexist language. The article suggests certain changes in the language of the Confession of Belhar in order to include women. Furthermore, it explores possible ways in which a confession with healthy insights into justice, such as the Confession of Belhar, can enhance the political and social wellbeing of women by reflecting the interconnectedness of people in its use of inclusive language.